Operasi Ekonomis dan Unit Commitment Pembangkit Thermal pada Sistem Kelistrikan Jambi - Delima .; Syafii . (Jurusan Teknik Elektro Universitas Andalas, 2016)
Economical operation at power plants is an important aspect in the management of power system economic operation, his specialty in this paper discusses economic and operating unit Commitment to coordination of power plant electrical systems Jambi by applying method of the list of priorities. The data used in this paper is thermal power plant in November 2015 conducted in Jambi province retrieved results less economical, for it is need for calculation of economical operations for power generation units. The selected combination is the combination that produces the most fuel costs to a minimum. On the imposition of 235 MW power by operating unit 4 generating namely PLTG Batanghari unit 1, PLTMG segai gelam unit 3, unit 6, Rent PLTG PLTG Batanghari unit 2. With operating expenses amounted to Rp.,65.102.864.238 method of the list of priorities in solving unit commitment gives results which are more optimal as compared to the total costs incurred by PT. PLN (Persero) Area Of Jambi. The total cost of the plant from PT. PLN (Persero) Rp Jambi Region. 163,755,996.30 thus there are savings of Rp. 60,891,757.65. per mounth From the results of this data processing operations are economical in power plants in Jambi province need to be rethought to make it more efficient in the use of electrical energy.Keywords : Optimization of plant scheduling, economical operation, Combination of on / off priority list. Abstrak - Operasi ekonomis pada pembangkit tenaga listrik merupakan suatu aspek penting dalam manajemen sistem tenaga listrik khusus nya operasi ekonomis, dalam makalah ini membahas tentang operasi ekonomis dan unit Commitment untuk koordinasi pembangkit sistem kelistrikan Jambi dengan menerapkan metode daftar prioritas. Data yang digunakan dalam makalah ini adalah pembangkit listrik tenaga termal pada bulan November 2015 dilakukan di Provinsi Jambi diperoleh hasil kurang ekonomis, untuk itu perlu adanya perhitungan pada operasi ekonomis untuk unit-unit pembangkit. Kombinasi yang dipilih adalah kombinasi yang menghasilkan biaya bahan bakar yang paling minimum. Pada pembebanan daya 235 MW dengan mengoperasikan 4 unit pembangkit yaitu PLTG Batanghari unit 1, PLTMG segai gelam unit 3, PLTG Sewa unit 6, PLTG Batanghari unit 2. Dengan biaya operasi sebesar Rp.102.864.238,65. Metode daftar prioritas dalam menyelesaikan permasalahan unit commitment memberikan hasil yang lebih yang lebih optimal dibandingkan dengan total biaya yang dikeluarkan oleh PT.PLN (Persero) Wilayah Jambi. Total biaya pembangkit dari PT.PLN (Persero) Wilayah Jambi Sebesar Rp. 163.755.996,30 dengan demikian ada penghematan sebesar Rp. 60.891.757,65./bulan. Dari hasil pengolah data ini maka operasi ekonomis pada pembangkit tenaga listrik di Provinsi Jambi perlu dikaji ulang agar lebih efesien dalam penggunaan energi listrik.Kata Kunci : Optimalisasi penjadwalan pembangkit , Operasi ekonomis, Kombinasi on/off daftar prioritas .